Study on Coupling and Coordination Time Series of County Urbanization and Water Environment ——Take Changshu,Jiangsu as an Example - RONG Jie; ZHANG Fengtai (Renmin Zhujiang)
This paper establishes an evaluation index system for the coordinated development of urbanization and water environment in Changshu and discusses their coupling and coordination relationship,so as to provide a reference for promoting the coordinated development of regional urbanization and water environment and formulating policies.In this paper,the weight of each index is calculated by using the coefficient of variation method.A coupling and coordination model is constructed to measure the time series characteristics of the coupling and coordinated development of the urbanization and water environment in Changshu from 2011 to 2020.The study finds that the comprehensive index of urbanization increases steadily,and that of water environment increases with fluctuations.The coupling and coordination degree between urbanization and water environment shows a rising trend.The two systems have gone through three stages of development during this period:since 2011,urbanization and water environment have undergone imbalance and decline;from 2012 to 2013,they entered transitional development and then coordinated development from 2014 to 2020.In 2011—2016,urbanization lagged behind the water environment;in 2017,urbanization and water environment were balanced;in 2018—2020,water environment lagged behind urbanization.In the future development,it is necessary to grasp the law of coupling and coordination,adopt the urban development model of adjusting measures to local conditions and time,and focus on building a Jiangnan area with a favorable water environment.